IR Leadership in the Digital Institution. Issue 178 (23rd November 2018) - Cantwell, Bethan L.; Richter, Susan M.
Abstract: A successful IR leader in the digital institution requires effective communication skills to articulate institutional goals, as well as to collaborate with multiple groups for the design and management of operational tasks. This chapter examines the needed skills of senior IR professionals and how these skills apply within a digital institution.